Nutritional disorders associated with management errors in Psittaciformes (Research, Society and Development, 2020)
Psittacines are birds of the order Psittaciformes characterized by a curved upper beak adapted to their food, which in nature, is generally made up of seeds, sprouts, chestnuts, coconut, fruits, flowers, nectar, proteins and other vegetables. The objective of this study is to analyze the main nutritional errors related to Pisittaciformes kept as a pet. It is an integrative literature review with search for articles in the following databases: Scientific Electronic Library Online (SCIELO); Medical Literature Analysis and Retrieval System Online (MEDLINE) and Latin American and Caribbean Literature in Health Sciences (LILACS), using the descriptors: Disturbances; Psittaciformes; and Nutrition. The selection followed the inclusion / exclusion criteria of articles from the last 5 years, in Portuguese, English and Spanish. Studies that were inconclusive and / or repetitive were excluded. The results showed that psittacines are the most desired birds as a pet, however restrictive and inadequate handling and nutrition conditions end up leaving these animals in constant stress resulting in several nutritional disorders such as obesity, hypovitaminosis A, calcium and protein deficiency and other pathologies. Thus, further studies on the nutrition of parrots are necessary in order to reduce the disorders resulting from their management errors.